Symptoms of post-traumatic stress disorder in parents of preterm newborns: A systematic review of interventions and prevention strategies - Laccetta, Gianluigi; Di Chiara, Maria; De Nardo, Maria Chiara; Terrin, Gianluca (Frontiers in Psychiatry, 2023)
Background Preterm birth and subsequent NICU admission can be a traumatic experience for parents who may subsequently develop post-traumatic stress (PTS) disorder (PTSD). Given that developmental issues are common among children of parents with PTSD, interventions for prevention and treatment are essential. Objective To assess the most effective non-pharmacological interventions to prevent and/or treat PTS symptoms in parents of preterm newborns. Methods Systematic review performed in accordance with the PRISMA statements. Eligible articles in English language were searched in MEDLINE, Scopus, and ISI Web of Science databases using the following medical subject headings and terms: “stress disorder, post-traumatic”, “parents”, “mothers”, “fathers”, “infant, newborn”, “intensive care units, neonatal”, and “premature birth”. The terms “preterm birth” and “preterm delivery” were also used. Unpublished data were searched in ClinicalTrials.gov website. All intervention studies published until September 9th, 2022 and including parents of newborns with gestational age at birth (GAb) <37 weeks which underwent ≥1 non-pharmaceutical interventions for prevention and/or treatment of PTS symptoms related to preterm birth were included. Subgroup analyses were conducted by type of intervention. The quality assessment was performed according to the criteria from the RoB-2 and the “NIH Quality Assessment Tool for Before-After studies”. Results 16628 records were identified; finally, 15 articles (1009 mothers, 44 fathers of infants with GAb ≤366/7 weeks) were included for review. A good standard of NICU care (effective as sole intervention: 2/3 studies) and education about PTSD (effective in association with other interventions: 7/8 studies) could be offered to all parents of preterm newborns. The 6-session Treatment Manual is a complex intervention which revealed itself to be effective in one study with low risk of bias. However, the effectiveness of interventions still remains to be definitively established. Interventions could start within 4 weeks after birth and last 2-4 weeks. Conclusion There is a wide range of interventions targeting PTS symptoms after preterm birth. However, further studies of good quality are needed to better define the effectiveness of each intervention.